More than sport: A social-identity intervention to support transitions out of elite sport - Young, T.; Haslam, C.; Coffee, P.; Cooper, D.; McAulay, C.; Hartley, C.; Mertens, N.; Luong, M.; La Rue, C.; Haslam, S. A.; Steffens, N. K.; Cruwys, T.; et al. (Psychology of Sport and Exercise, 2024)
Elite athletes often make large personal sacrifices to pursue excellence, but there is insufficient support for them when they leave elite sport. Identity loss is central to athletes` transition trajectories and hence the management of identity change is a crucial area for support. The More Than Sport (MTS) program is a novel digital intervention that aims to provide this support—helping athletes manage identity change in the process of leaving elite sport. The present research aims to study elite athletes` experiences with the MTS program and their perceptions of its usefulness in managing the transition away from elite sport. We undertook a qualitative study with athletes (N=25) from three countries (the United Kingdom, Australia and Belgium) using reflexive thematic analysis to explore their experiences of the program and their feedback on program content. We identified three key themes and eight subthemes. The first key theme was Value of the Program, and this was underpinned by four sub-themes that centred on Program importance and novelty, how Positive and confronting experiences afford insight, the Value of developing shared understanding, and Realising the value of social groups. The second key theme was Engagement with Program Elements and here participants commented on Program content and Delivery format. The final key theme was Time and Place for Identity Management Programs which included the sub-themes of Optimal timing and Additional program beneficiaries. Overall, the results highlight the value of MTS specifically, and identity management efforts more broadly, to help elite athletes adjust successfully to life beyond sport.